"Satan's Minions" and "True Believers": How Criminal Defense Attorneys Employ Quasi-Religious Rhetoric and What It Suggests about Lawyering Culture. (25th July 2022) - Webster, Elizabeth; Powell, Kathleen; Lageson, Sarah E.; Baćak, Valerio
Abstract: The notion of law as sacred, and lawyers as righteous saviors, may seem anachronistic in the current context of heavy caseloads and expedited processing in the criminal justice system. Nevertheless, language reflecting these ideals still permeates defense attorneys' descriptions of their roles, their legal practice, and their relationships to their colleagues and adversaries. We examine this language – specifically, attorneys' quasi-religious rhetoric – to better understand courtroom dynamics: how attorneys see themselves, their work, their colleagues, and their legal adversaries. In this analysis of semi-structured interviews with 30 defense attorneys, we find that attorneys use of quasi-religious rhetoric manifests as a cultural practice that helps to establish and maintain professional identities, boundaries, and relationships. Our findings also suggest that young and novice public defenders are likely to express especially zealous views, which may compromise their efforts to collaborate within the adversarial system, as well as contribute to burnout.